Survey of antipsychotic medication curriculum content in Australian university nursing programmes - Morrison, P.; Stomski, N.; Mcallister, M.; Wynaden, Dianne; Hungerford, C.; Usher, K.; Maude, P.; Crowther, A.; Batterbee, R. (Wiley-Blackwell Publishing Asia, 2017)
Antipsychotic medication has long been one of the first-line interventions for people with serious mental illness, with outcomes including reductions in symptoms and relapse rates. More recently, however, questions have been raised about the efficacy of antipsychotic medications, especially in light of their side-effect profile. Such questions have implications for the nurses administering antipsychotic medications, particularly in relation to their knowledge of the antipsychotic medication, its efficacy, and side-effect profile. Also important is the education of nursing students about antipsychotic medications, their use, and management. The present study reports findings of research that explored current curriculum content concerning psychopharmacological treatment in Australian undergraduate and postgraduate nursing programmes. Using a survey design, the research examined the content and modes of delivery of this content to gauge how well students are prepared for administering antipsychotic medication to people with serious mental illness. Findings of the research suggested the need for improvement in preparing nursing students to administer antipsychotic medication, including indications, contraindications, as well as recognition and management of side-effects.